Breastfeeding in a patient with chronic myeloid leukemia during tyrosine kinase inhibitor therapy. (April 2021) - Terao, Ryuta; Nii, Mitsumaro; Asai, Hiroko; Nohara, Fumikatsu; Okamoto, Toshio; Nagaya, Ken; Azuma, Hiroshi
Introduction: Although imatinib is the first-line of therapy for Philadelphia chromosome (Ph)-positive chronic myeloid leukemia (CML), in Japan, it is recommended by the manufacturer that lactating women treated with imatinib mesylate for CML should discontinue breastfeeding their infants. Case: A 32-year-old pregnant patient was diagnosed with Ph-positive CML at 13 weeks of gestation. She received imatinib (400 mg/day) after 28 weeks of gestation. A female infant was delivered at a gestational age of 35 weeks and 3/7 days after preterm premature rupture of membranes. It was decided to feed only colostrum to the infant and formula feeding was done subsequently because of the risk of the transfer of imatinib to breast milk. The milk/plasma (M/P) ratio and the relative infant dose (RID) for imatinib were calculated to be 0.35 and 1.4%, respectively at 5 days of life. Moreover, the serum level of imatinib in the child of age 5 days was 27 ng/mL, which was much lower than the target trough value for CML (1000 ng/mL). Conclusion: The M/P ratio and RID values for maternally administered imatinib were within the safe range for breastfeeding, as reported in previous studies. In addition, it was found that the serum concentration of imatinib in the child was relatively low during short-term breastfeeding.